2010
DOI: 10.2337/db10-0014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Insulin in the Ventromedial Hypothalamus on Pancreatic Glucagon Secretion In Vivo

Abstract: OBJECTIVEInsulin released by the β-cell is thought to act locally to regulate glucagon secretion. The possibility that insulin might also act centrally to modulate islet glucagon secretion has received little attention.RESEARCH DESIGN AND METHODSInitially the counterregulatory response to identical hypoglycemia was compared during intravenous insulin and phloridzin infusion in awake chronically catheterized nondiabetic rats. To explore whether the disparate glucagon responses seen were in part due to changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 54 publications
(76 reference statements)
6
73
2
Order By: Relevance
“…These effects were blocked by coinfusion of PI3K inhibitors into the ICV. Further studies also showed that intrahypothalamic insulin administration suppressed pancreatic glucagon release under hypoglycemic clamp conditions in rats (25).…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 99%
“…These effects were blocked by coinfusion of PI3K inhibitors into the ICV. Further studies also showed that intrahypothalamic insulin administration suppressed pancreatic glucagon release under hypoglycemic clamp conditions in rats (25).…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 99%
“…For example, insulin acts indirectly via insulin receptors expressed on the ventromedial hypothalamus to modulate peripheral glucose homoeostasis in addition to its direct action on target tissues (Diggs-Andrews et al 2010, Paranjape et al 2010. We therefore proposed the hypothesis that the inhibitory effect of SST on insulin release may similarly be at least partly dependent on central activation of SSTRs by SST.…”
Section: Discussionmentioning
confidence: 98%
“…Loss of insulin signaling in neurons expressing Glut4 markedly increases hyperglycemia in mice with peripheral insulin resistance (18). Furthermore, in nondiabetic rats, acute blockade of insulin signaling within the ventromedial hypothalamus, a key glucose-sensing region, immediately stimulates glucagon secretion (7). Impaired insulin secretion also appeared in preliminary studies using virus-induced knockdown of ventromedial hypothalamus InsR (R.S.…”
Section: Making Sense Of the Datamentioning
confidence: 91%
“…Further improvements of INS1 cells in terms of insulin content and secretion were then obtained with clonal selection techniques to obtain a cell line called 823/13 (6). In work going on in parallel, the oncogene simian virus 40 large tumor antigen (SV40LT) was first used to make cells with β cell characteristics when HIT cells were generated from infected isolated islets from hamsters (7). Work in mice with the same oncogene then led to the generation of βTC cells (8) and MIN6 cells (9), which remain among the most widely used rodent pancreatic β cell lines today.…”
Section: Lessons From 30 Years Of Work In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation